THE EFFECTIVENESS OF DRAMA STRATEGY TO ENHANCE STUDENTS' SPEAKING SKILL - Yogi Rivaldo Ananta (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
ABSTRACT Ananta, Y. R .2021.The Effectiveness of Drama Strategy to Enhance Students’ Speaking Skill. Skripsi, English Education Department, Faculty of Teacher Training and Education, University of Islam Malang.Advisor : (I) Dr. Alfan Zuhairi,M.Pd (II) Febti Ismiatun, S.Pd,M.Pd Key words: English Drama Strategy, Group Presentation, SpeakingDrama is experimential learning that engaged mind, body, voice, and emotions to interpret and convey to others information and ideas. Drama technique can improve students’ communicative skills. It will engage the students to be more active.This study investigated the effectiveness of using English drama to enhance students’ speaking skill in tenth grade students at NU PAKIS Senior High School Malang. The participants of this study consist of 60 students. This study used quasi experimental research design. The researcher used a speaking test as the instrument to collect the data. There are pre test and post test. The data was analyzed using Mann Whitney test to find out any significant differences between experimental and control group in terms of speaking performance. The result of Mann Whitney test found that the sig. value was lower than 0.05, that is 0.003 (0.003 < 0.05), which means the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that English drama had significant effect in students speaking skill rather than using group presentation. Furthermore, the mean rank of experimental group was higher than control group (69.07 > 61.67) and the experimental students have better speaking than control group.Based on the result, the researcher concluded that English drama strategy gave significant contribution to enhance the students' speaking skill and the English drama strategy could be an effective method to teach speaking. The findings showed that there are some significant differences between students who are treated by English drama and students who are treated group presentation strategy on students’ speaking skill in ten grade Senior High School students at NU PAKIS Senior High School Malang.The application of drama into the language classroom practices is, yet, probably challenge, the nature of drama-based role plays need to be considered and presented by the English teachers in their instructional learning so as to allow students to take greater responsibility for their learning in dynamic, engaging, interactive and meaningful ways.